THE USE OF TECHNOLOGY FOR INDONESIAN STUDENTS’ ASSIGNMENT COMPLETION - Mutiara Laya, Nihta Liando , Mister Gidion Maru (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This research aims at figuring out the use of technology in the assignment completion. The study further explores how technology assists students to finish the assignment or tasks given to them. The technology in this context refers to students’ use of smartphones, laptop and LCD as well as internet infrastructure. the data for this study are gained by carrying out semi-structure interview with ten students of 8A Class at SMP Muhammadiyah 1 Manado, North Sulawesi, Indonesia. These ten students as the respondents are taken due to their possession and familiarity the technology used for learning purposes. This research found that technology acts as an effective tool to maintain students’ participation. Further, teachers become the key success on the application of technology at schools. Students show a positive response on the application of technology in learning because it enables them to minimize mistakes, spend less time to complete the tasks, and improve their confidence in expressing their ideas as required in the assignment.